Adiponectin inhibits the activation of lung fibroblasts and pulmonary fibrosis by regulating the nuclear factor kappa B (NF-κB) pathway. Issue 4 (1st April 2022) - Wang, Xin; Yang, Jian; Wu, Liangquan; Tong, Chunran; Zhu, Ying; Cai, Wei; Wan, Bing; Zhang, Xiuwei
ABSTRACT: Idiopathic pulmonary fibrosis (IPF) is a common pulmonary interstitial disease with a high mortality rate. Adiponectin (APN) is reportedly an effective therapy for fibrosis-related diseases. This study aimed to investigate the potential effects of APN on IPF. Male BALB/c mice were injected with bleomycin (BLM) and treated with different doses of APN (0.1, 0.25, and 0.5 mg/kg). The body weights of the mice were recorded. Immunohistochemical, hematoxylin and eosin, and Masson staining were performed to evaluate pulmonary histopathological changes. Enzyme-linked immunosorbent assay (ELISA) and western blotting were performed to assess tissue inflammation. The human lung fibroblasts HELF were stimulated with TGF-β1 and treated with different doses of APN (2.5, 5, and 10 μg/ml). Cell proliferation, inflammation, and fibrosis were determined by MTT assay, EdU assay, colony formation assay, ELISA, and western blotting. APN significantly attenuated BLM-induced body weight loss, alveolar destruction, and collagen fiber accumulation in mice ( p < 0.05). APN decreased the expression of α-SMA and collagen I and reduced the concentration of TNF-α, IL-6, IL-1β, and IL-18 in lung tissues ( p < 0.05). In TGF-β1-treated HELF cells, cell proliferation and colony formation were inhibited by APN ( p < 0.05). Additionally, the expression of α-SMA, collagen I, and pro-inflammatory cytokines were suppressed by APN ( p < 0.05). APN inhibited the phosphorylation of IκB and nuclear translocation of p65. In conclusion, these findings suggest that APN is an effective agent for controlling IPF progression. The antifibrotic effects of APN might be mediated via inhibiting the NF-κB signaling pathway. Graphical Abstract: uf0001